Otto neurath and the unity of science - Symons, John.; Pombo, Olga.; Torres, Juan Manuel, 1947-.; SpringerLink (Online Service). (Dordrecht Springer, 2011)
This volume critically reexamines Otto Neurath?s conception of the unity of science. Some of the leading scholars of Neurath?s work, along with many prominent philosophers of science critically examine his place in the history of philosophy of science and evaluate the relevance of his work for contemporary debates concerning the unity of science.
Preface; John Symons--Introduction ; Olga Pombo and Juan Torres--Part 1 - Neurath--Unity of Science and Logical Empiricism; Otto Neurath--The Neurath-Horkeimer-Controversy Reconsidered. Otto Neurath's Erwiderung to Max Horkeimer's Attack against the Vienna Circle; Karlheinz Barck--Otto Neurath's Epistemology and Its Paradoxes; Jan Sebestik--Neurath and the Encyclopaedic Project of the Unity of Science; Olga Pombo--Principles and Practices of Neurath's Language ; Ahti-Veikko Pietarinen--Conceptions of Reality - Schlick, Carnap, Neurath ; Thomas Bonk--Keeping Track of Neurath's Bill : Abstract Concepts, Stock Models and the Unity of Classical Physics ; Sheldon Steed, Gabriele Contessa and Nancy Cartwright--G. Itelson - A Socratic Philosopher ; Gideon Freudenthal and Tatiana Karachentsev--Part 2 ? Unity--Unity without Myths; Daniel Andler--Two Unification Strategies: Analysis or Reduction, and Synthesis or Integration; Mario Bunge--A Comprehensible World; Robert L. Causey--Unified Science? Does Scientific Progress Necessarily Lead to a Unified Science ; C. Ulises Moulines--The Achilles' Heel of the Program for the Unity of Science; Juan Manuel Torres--Scientific Reasonableness and the Pragmatic Approach to the Unity of Science; Andrés Rivadulla--Naturalism and the Unity of Science; Jan Wolenski--Searching the Unity of Science: From Classical Logic to Abductive Logical Systems; Angel Nepomuceno, Fernando Soler, Atocha Aliseda--Direct Abduction through Dual Resolution; Fernando Soler, Angel Nepomuceno--Index.
Keywords: Science -- methodology; Science -- Language; Neurath, Otto -- 1882-1945.; Electronic books